Fast and sensitive UHPLC methods with fluorescence and tandem mass spectrometry detection for the determination of tetracycline antibiotics in surface waters - Škrášková, Karolina; Santos, Lúcia H M L M; Šatínský, Dalibor; Pena, Angelina; Montenegro, Maria Conceição B S M; Solich, Petr; Nováková, Lucie (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2013)
In this paper two fast and highly sensitive ultra-high performance liquid chromatography (UHPLC) methods for the determination of tetracycline antibiotics (oxytetracycline, tetracycline, doxycycline, demeclocycline, chlortetracycline, minocycline and degradation product epitetracycline) in surface waters have been developed using fluorescence (FL) and mass spectrometry (MS) detection. ACQUITY UPLC BEH C8 and ACQUITY CSH C18 columns were employed for FL and MS detection, respectively, both packed with 1.7μm particles. Mixed-mode separation mechanism of CSH (charged surface technology) sorbent was found particularly useful in analysis of TCs, which possess problematic amphoteric structures. The FL methodology was based on chelation of tetracyclines with calcium ions to perform on-column derivatisation. The developed methods were compared in the terms of validation parameters including linearity, sensitivity, precision and accuracy. The linearity range for FL detection was within 7ngmL(-1) to 50μgmL(-1) with method limit of detection (MLOD) as low as 0.2ngmL(-1) for most of the analytes. MS detection showed even higher sensitivity reaching MLOD of 0.003ngmL(-1), which is the highest sensitivity reported so far in analysis of TCs. Matrix matched calibration curves in the range of 0.01-50ngmL(-1) were used for quantification to compensate for matrix effects with the correlation coefficients demonstrating good linearity (0.9940-0.9999). The extraction of the antibiotics from surface waters was performed using solid phase extraction with Oasis HLB cartridges. Accuracy was expressed as recovery with values ranging from 96.52% to 127.30% and from 91.66% to 123.70% for FL and MS detection, respectively.
Keywords: Solid Phase Extraction; chemické látky znečišťující vodu; Linear Models; tetracykliny; Water Pollutants, Chemical; Tandem Mass Spectrometry; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Rivers; Sensitivity and Specificity; Anti-Bacterial Agents; senzitivita a specificita; lineární modely; fluorescenční spektrometrie; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; Tetracyclines; tandemová hmotnostní spektrometrie; řeky; extrakce na pevné fázi; antibakteriální látky; Spectrometry, Fluorescence